Long‐Term Biomass Yield and Species Composition in Native Perennial Bioenergy Cropping Systems. (1st September 2015) - Jungers, Jacob M.; Clark, Adam T.; Betts, Kevin; Mangan, Margaret E.; Sheaffer, Craig C.; Wyse, Donald L.
Abstract : Biomass yield is an important factor when recommending native perennial plants and mixtures for bioenergy production. Our objective was to determine long‐term biomass yields in fertilized and unfertilized native plant monocultures and mixtures that show promise for bioenergy across diverse environments in the Upper Midwest. We measured biomass yields, species composition, and diversity annually in monocultures and mixtures ranging from 4 to 24 planted species including grasses, legumes, and other forbs; each managed with and without 67 kg N ha −1 fertilizer applied annually at nine locations for 7 yr. Without N fertilization, switchgrass ( Panicum virgatum L.) monocultures and an eight‐species mixture of grasses and legumes produced the most biomass over locations and years (5.1 Mg ha −1 ). With N fertilizer, switchgrass monocultures and a four‐species mixture of grasses produced the highest yields (6.8 and 6.4 Mg ha −1 ). Over time, biomass yields increased for switchgrass, decreased for Canada wild rye ( Elymus canadensis L.), and remained stable for the high diversity mixtures. Other mixtures had nonlinear changes in yield, likely related to changes in species composition. Although the relative abundance of individual species changed over time, Shannon diversity was constant except for the four‐species legume mixture where it decreased. Contrary to other studies, N fertilization did not decrease species diversity through time. Diversity was positively related to biomass yield following establishment, but the strength of the relationship diminished with stand age. Native plant mixtures managed with and without N fertilizer can yield similar biomass compared with highly productive monocultures in the Upper Midwest.